(3GdLhGgQ GdNeSs - (3GHf NWjQ GdOjf , eMeO Hf NWjQ Hf HGjRjO GdYWGQ, CHh GdeDjO,J (B970 (3g` s ((3jMji Hf aJjGf s)
(3ChdgG (B:s
(3GdcGed GdTGed ajgG ChLO GdLhGgQ GdNeSI GdNhGfS GdNeSI GdJj bGd ajgG adG CbSe HGdNfS GdLhGQ GdcfS s
(3BNQgG (B:s
(3efHY GdBKGQ heWdY GdCfhGQ gj GdeJhLg Edjg Hcd hLg hgh GdcHjQ GdeJYGd Je s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B114 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B282s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B614s
Keywords: (3GdJUha hGdBOGH GdTQYjIs